Toward the Next Generation of U.S. National Longitudinal Surveys - Adam Gamoran (SAGE Publishing, 2016)
In fall 2013, the National Center for Education Statistics (NCES) hosted a group of researchers to provide input into its program of longitudinal surveys. Organized by the National Academy of Education with a grant from the Institute of Education Sciences, the Workshop to Examine Current and Potential Uses of NCES Longitudinal Surveys by the Education Research Community addressed issues of new designs, new measures, persisting issues, and technologies that could introduce new approaches. Findings from the workshop have appeared in AERA Open and on the National Academy of Education's website and have been discussed at the American Educational Research Association annual meeting. This paper provides a background to the workshop, highlights key findings, and discusses the responses of NCES to researcher input in the context of constraints that limit NCES's ability to introduce change. These issues deserve widespread attention in light of the importance of NCES longitudinal surveys as a resource for education research.